Buyer and Supplier Activation - Guide : Electronic Government Procurement - Asian Development Bank; Inter-American Development Bank; World Bank (World Bank, Washington, DC, 2014)
This guide concerns the challenges, implementation, and training connected to the introduction of electronic government (e-GP) procurement. A successful strategy for e-GP requires that a marketplace be created. The idea of a marketplace differs between countries but for the purposes of this discussion recognises that e-GP requires that government buyers and suppliers (either contracted or uncontracted) come together and interact online, where previously they interacted through diverse means including newspapers, faxes, written correspondence, etc. In the transition to e-GP, buyers will need to learn new job skills and undergo some reorientation to procurement as a strategic function. Activation of suppliers too is critical to the implementation of e-GP. Attracting a wider range of suppliers to the government procurement market is an important success factor in strategic procurement planning. Training requirements for buyers exist at two levels. The first is procurement career development for those who will manage e-GP. If procurement is to be managed as a strategic issue then the fact that procurement staff are often a population that has received little training needs to be addressed. The second training requirement is to address the needs of staff who will be involved in the day to day operation of the e-procurement process. A summary of some of the training agenda is outlined in the annexes of this guide.